When does the multiple principals hypothesis hold? The politics of U.S. agency policymaking autonomy. Issue 1 (5th January 2021) - Palus, Christine K.; Yackee, Susan W.
Abstract: When the bureaucracy's political principals hold different preferences for policy, does this increase the bureaucracy's policymaking autonomy? Existing theory strongly suggests "yes." We, however, argue that this pattern will materialize only when the bureaucracy's principals are all on the same side of the political divide. (i.e., unified government). Using data gathered from the American states at two time points, we capture preference divergence by measuring the ideological distance between the bureaucracy's key political principals—legislators, governors, and courts—on the common left–right dimension. We measure policymaking autonomy through multi‐faceted surveys of state agency leaders. In keeping with our argument, we demonstrate that greater preference divergence across the bureaucracy's principals is associated with increased agency policymaking autonomy under unified—but not under divided—government. The results shed new light on when, and why, the bureaucracy's political principals may provide an oversight check on the policymaking power of the modern administrative state.